2016
DOI: 10.1155/2016/7214932
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Spatial Chromium Contamination of the Environment around Industrial Zones

Abstract: This study was conducted to determine the spatial levels of chromium contamination of water, agricultural soil, and vegetables in the leather tanning industrial areas using spectrophotometric methods. The results showed elevated accumulation of total Cr ranging from 10.85 ± 0.885 mg/L to 39.696 ± 0.326 mg/L, 16.225 ± 0.12 mg/Kg to 1581.667 ± 0.122 mg/Kg, and 1.0758 ± 0.05348 mg/Kg to 11.75 ± 0.206 mg/Kg in water, agricultural soil, and vegetable samples, respectively. The highest levels of chromium (VI) found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
2
20
5
1
Order By: Relevance
“…The value of total Cr (22.6 mg/kg) in the soil sample of this study was much lower than the values reported in Homa et al (254.25-1581.66 mg/kg) [15] as well as the permissible limit (100 mg/kg) by WHO and FAO. The total Cr, Cr(III), and Cr(VI) which were obtained in the lettuce plant samples were also lower than those reported by Homa et al (7.4163-10.473, 7.3913-10.36, and 0.025-0.113 mg/kg, resp.)…”
Section: The Potential Pollution Effect Of the Kombolcha Tannerycontrasting
confidence: 82%
See 4 more Smart Citations
“…The value of total Cr (22.6 mg/kg) in the soil sample of this study was much lower than the values reported in Homa et al (254.25-1581.66 mg/kg) [15] as well as the permissible limit (100 mg/kg) by WHO and FAO. The total Cr, Cr(III), and Cr(VI) which were obtained in the lettuce plant samples were also lower than those reported by Homa et al (7.4163-10.473, 7.3913-10.36, and 0.025-0.113 mg/kg, resp.)…”
Section: The Potential Pollution Effect Of the Kombolcha Tannerycontrasting
confidence: 82%
“…The concentration of Cr(III) is also extremely higher than the reported value by Homa et al (19.126-39.374 mg/L) [15]. Moreover, the amount of Cr(VI) obtained in this study at the discharging point was higher than that of Homa et al (0-0.322 mg/L) [15]. In the downstream case, all chromium species were lower than other reported values.…”
Section: The Potential Pollution Effect Of the Kombolcha Tannerycontrasting
confidence: 81%
See 3 more Smart Citations